Trendbericht Organische Chemie 2022 - Andexer, Jennifer N.; Beifuss, Uwe; Brasholz, Malte; Breinbauer, Rolf; Breugst, Martin; Dumele, Oliver; Ernst, Martin; Ganardi, Ruth; Giese, Michael; Gulder, Tobias A. M.; Hüttel, Wolfgang; Kath‐Schorr, Stephanie; et al. (Nachrichten aus der Chemie)
Keywords: General Chemical Engineering; General Chemistry

Synthesis of Cyclic Carbonates Catalyzed by CaI2–Et3N and Studies on Their Biocatalytic Kinetic Resolution - Terazzi, Constanza; Laatz, Karoline; von Langermann, Jan; Werner, Thomas (ACS Sustainable Chemistry and Engineering)
Keywords: T1; T3; CSSD

Synthesis of Bifunctional Phosphonium Salts Bearing Perfluorinated Side Chains and Their Application in the Synthesis of Cyclic Carbonates from Epoxides and CO 2 - Ren, Changyue; Spannenberg, Anke; Werner, Thomas (Asian Journal of Organic Chemistry)
Keywords: T1; T2; CSSD

Organische Chemie - Paradies, Jan; Andexer, Jennifer; Beifuss, Uwe; Beuerle, Florian; Brasholz, Malte; Breinbauer, Rolf; Ernst, Martin; Ganardi, Ruth; Gulder, Tobias A. M.; Hüttel, Wolfgang; Kath‐Schorr, Stephanie; Körber, Karsten; et al. (Nachrichten aus der Chemie)
Keywords: General Chemical Engineering; General Chemistry

Catalytic, Kinetic, and Mechanistic Insights into the Fixation of CO2 with Epoxides Catalyzed by Phenol‐Functionalized Phosphonium Salts - Hu, Yuya; Wei, Zhihong; Frey, Anna; Kubis, Christoph; Ren, Chang‐Yue; Spannenberg, Anke; Jiao, Haijun; Werner, Thomas (ChemSusChem)
Keywords: T1

Base-Free Catalytic Wittig-/Cross-Coupling Reaction Sequence as Short Synthetic Strategy for the Preparation of Highly Functionalized Arylbenzoxepinones - Werner, Thomas; Grandane, Aiga; Pudnika, Linda; Domraceva, Ilona; Zalubovskis, Raivis (Synthesis)
Abstract The facile synthesis of highly functionalized building blocks with potential biological activity is of great interest to medicinal chemistry. The benzoxepinone core structures commonly exhibit biological activity. Thus, a short and efficient synthetic route towards benzoxepine containing scaffold, which enables late stage modification was developed. Namely, base-free catalytic Wittig reactions enabled the synthesis of bromobenzoxepinones from readily available starting materials. Subsequent, Suzuki–Miyaura and Stille reactions proved to be suitable methods to access a variety of benzoxepinone diaryl derivatives by late stage modification in only three steps. This three-step reaction sequence is suitable for high throughput applications and gives facile access to highly complex molecular structures, which are suitable for further functionalization. The antiproliferative properties of selected arylbenzoxepinones were tested in vitro on monolayer tumor cell line A549. Notably, in this initial screening, these compounds were found to be active in the micromolar range.
Keywords: T2; T4; CSSD

Indirect reduction of CO2 and recycling of polymers by manganese-catalyzed transfer hydrogenation of amides, carbamates, urea derivatives, and polyurethanes - Liu, Xin; Werner, Thomas (Chemical Science)
A Mn–PNP complex proved to be a suitable catalyst for the transfer hydrogenation of amides, carbamates, urea derivatives and even polyurethanes.
Keywords: T1; T3; CSSD

Poly(methylhydrosiloxane) as a reductant in the catalytic base-free Wittig reaction - Tönjes, Jan; Longwitz, Lars; Werner, Thomas (Green Chemistry)
PMHS proved to be a suitable terminal reductant for P(iii)/P(v) redox cycling with a methyl-substituted phosphetane as catalyst and BuOAc as solvent. The formation of water by silanol condensation was identified as main pathway of siloxane formation.
Keywords: T2; CSSD

AMPA-15N – Synthesis and application as standard compound in traceable degradation studies of glyphosate - Wirth, Marisa A.; Longwitz, Lars; Kanwischer, Marion; Gros, Peter; Leinweber, Peter; Werner, Thomas (Ecotoxicology and Environmental Safety)
Keywords: T4; CSSD

Selective Construction of C−C and C=C Bonds by Manganese Catalyzed Coupling of Alcohols with Phosphorus Ylides - Liu, Xin; Werner, Thomas (Advanced Synthesis and Catalysis)
Keywords: T1; T3; CSSD

Organische Chemie - Andexer, Jennifer N.; Beifuss, Uwe; Beuerle, Florian; Brasholz, Malte; Breinbauer, Rolf; Ernst, Martin; Greb, Julian; Gulder, Tobias; Hüttel, Wolfgang; Kath‐Schorr, Stephanie; Kordes, Markus; Lehmann, Matthias; et al. (Nachrichten aus der Chemie)
Keywords: General Chemical Engineering; General Chemistry

Erbium-Catalyzed Regioselective Isomerization–Cobalt-Catalyzed Transfer Hydrogenation Sequence for the Synthesis of Anti-Markovnikov Alcohols from Epoxides under Mild Conditions - Liu, Xin; Longwitz, Lars; Spiegelberg, Brian; Tönjes, Jan; Beweries, Torsten; Werner, Thomas (ACS Catalysis)
Keywords: T3; CSSD

Catalytic Systems for the Synthesis of Biscarbonates and Their Impact on the Sequential Preparation of Non-Isocyanate Polyurethanes - Wulf, Christoph; Reckers, Matthias; Perechodjuk, Anna; Werner, Thomas (ACS Sustainable Chemistry and Engineering)
Keywords: T1; T3; CSSD

Plasma‐Assisted Immobilization of a Phosphonium Salt and Its Use as a Catalyst in the Valorization of CO 2 - Hu, Yuya; Peglow, Sandra; Longwitz, Lars; Frank, Marcus; Epping, Jan Dirk; Brüser, Volker; Werner, Thomas (ChemSusChem)
Keywords: T2; T1; CSSD

Benzoxepinones: A new isoform-selective class of tumor associated carbonic anhydrase inhibitors - Grandane, Aiga; Nocentini, Alessio; Werner, Thomas; Zalubovskis, Raivis; Supuran, Claudiu T. (Bioorganic and Medicinal Chemistry)
Keywords: T4; T2; CSSD

Phosphetane Oxides as Redox Cycling Catalysts in the Catalytic Wittig Reaction at Room Temperature - Longwitz, Lars; Spannenberg, Anke; Werner, Thomas (ACS Catalysis)
Keywords: T2; CSSD

Trendbericht Organische Chemie - Andexer, Jennifer N.; Beifuss, Uwe; Beuerle, Florian; Brasholz, Malte; Breinbauer, Rolf; Ernst, Martin; Gulder, Tobias A. M.; Kath‐Schorr, Stephanie; Kordes, Markus; Lehmann, Matthias; Lindel, Thomas; Lüdeke, Steffen; et al. (Nachrichten aus der Chemie)
Keywords: General Chemical Engineering; General Chemistry

Transfer hydrogenation of cyclic carbonates and polycarbonate to methanol and diols by iron pincer catalysts - Liu, Xin; de Vries, Johannes G.; Werner, Thomas (Green Chemistry)
The reduction of poly and cyclic carbonates in the presence of an earth abundant metal catalyst using isopropanol as the hydrogen donor is reported.
Keywords: T3; CSSD

Life Cycle Assessment for the Organocatalytic Synthesis of Glycerol Carbonate Methacrylate - Büttner, Hendrik; Kohrt, Christina; Wulf, Christoph; Schäffner, Benjamin; Groenke, Karsten; Hu, Yuya; Kruse, Daniela; Werner, Thomas (ChemSusChem)
Keywords: T1; T4; CSSD

Polyethers as Complexing Agents in Calcium-Catalyzed Cyclic Carbonate Synthesis - Hu, Yuya; Steinbauer, Johannes; Stefanow, Vivian; Spannenberg, Anke; Werner, Thomas (ACS Sustainable Chemistry and Engineering)
Keywords: T1; T3; CSSD